Behavior of flexural members made from oil palm shell and clinker concrete / Md. Nazmul Huda - Md.Nazmul , Huda (2017)
Waste materials, such as oil palm shell (OPS) and palm oil clinker (POC) from the Malaysian palm oil industry have been used by various researchers to produce lightweight concrete. Concrete containing only OPS showed more ductility and low compressive strength while concrete containing only POC showed less ductility but high compressive strength. The combinations of OPS and POC in concrete seem to be able to improve the compressive strength and ductility behavior. In this study, the possibility of replacing the normal wight aggregate by a mixture of OPS and POC aggregates were investigated. Trial mixes using this mixture of aggregates were carried out to determine the optimum mix ratio. This research also investigated the engineering properties of the concrete mixes and the flexural performance of reinforced palm shell and clinker concrete (PSCC) beams. Seven PSCC mixes were considered. The proportions of OPS and POC in the concrete mixes were varied from 30% to 70%. In the concrete mix, cement content is kept 450 kg/m3 which is lowest among the published research so far. The optimum concrete mix was then used in the preparation of the PSCC beams. Eight singly reinforced PSCC beams of dimension 150 mm × 250 mm × 3300 with varying reinforcement ratios (0.50 to 2.11%) were prepared. The beams were loaded under four point bending until failure. The optimum concrete mix obtained from this study achieved compressive strength of about 46 MPa while the ductility index was about 3.56. Other engineering properties such as flexural strength, splitting tensile strength and modulus of elasticity showed good results for structural use. All PSCC beams exhibited typical flexural performance and experienced ductile failure by giving ample warning before failure. For the beams with higher reinforcement ratio, the deflections at service loads slightly exceeded the values suggested by EC2. The crack widths of PSCC beams satisfied the EC2 requirements for durability aspects. The ultimate moments from the experiment showed slight variations from those predicted by the EC2.